Lacustrine chlorophyll evolution at Central-Westernamazon basin during holocene - Soares, Juliano Henrique Fonseca (2024)
Amazonia Basin is responsible for regulating climate and providing moisture for both South and North hemisphere. Besides that, it presents to be one of the most productive areas in the globe and an important carbon sink. As a result of primary productivity, fossil pigments can be preserved in lake sedimentary records, becoming a valuable proxy for palaeoecological and climate changes. The concentration of chlorophyll derivatives is related to algal and plankton populations and consequently to levels of lake productivity. In this work, we compare the z-score values from the chlorophyll derivatives concentrations analyzed from sediment cores from nine lakes distributed over the Brazilian Amazon to create an evolutionary panorama of paleo productivity through Holocene. The climate in Amazon Basin has been variable over the last 11,500 years and these variations are registered in the lake's sedimentary records. The evolution of chlorophyll derivatives (SPDU) concentration in sediment cores, compared with a multiproxy approach, suggests a general increasing trend of moisture a productivity rate through the Holocene to the present. The relatively dry conditions in the early Holocene evolved to a much drier climate over the middle Holocene, becoming more humid through the late Holocene. These variations are well supported by chlorophyll derivatives concentrations, which indicates the evolution of lake primary productivity. The correlation can be traced, as well, by climate forcing exercising influence over Amazonia, as ITCZ, SACZ, SAMS, Solar Insolation, SST of tropical Atlantic and Pacific oceans, and ENSO, that confer wetter or drier conditions over the South America continent. Our results are also in good agreement with data of Ti from Cariaco Basin, 13C from Lake Titicaca, and the Black Carbon from biomass burning in Amazon, registered in Nevado Illimani. Therefore, the concentration of sedimentary pigments presents here to be a good proxy for paleoclimate change analysis, once the rise in productivity is closely linked to the increase in humidity conditions.